Analysis and prediction of unforced errors in men’s and women’s professional padel - Conde-Ripoll, Rafael; Muñoz, Diego; Sánchez-Alcaraz, Bernardino J.; Escudero-Tena, Adrián (Biology of Sport, 2024)
The aims were to I. assess the differences in unforced errors between men’s and women’s professional padel players, II. assess the differences in unforced errors between winners and losers of the set in professional padel players, III. analyse the evolution of unforced errors in professional padel. To do this, the unforced errors (which are provided by World Padel Tour (WPT)) were collected from 2,567 sets (1,476 men’s sets and 1,091 women’s sets) corresponding to matches from the final draw (round of 32, round of 16, quarterfinals, semi finals and finals) of tournaments on the WPT men’s and women’s circuits during 2016 to 2022 seasons, which are available on the WPT YouTube channel and on the WPT TV website. The results with respect to the first aim indicate that the number of unforced errors was higher in women’s padel than in men’s, regardless of the set number, tournament round, season and court. With respect to the second aim, not committing unforced errors is a fundamental factor in professional padel to win the sets. Finally, regarding the third aim, the number of unforced errors decreased as the seasons progressed; therefore, to win, players should not only have to pass the ball without missing, but they might have to hit winners or generate forced errors of the opponent.